Optimization of Normal Regimes of Power Transmission Lines - E. G. Pospelov; G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In order to optimize normal regimes of the power transmission lines notions of economic, maximum and the largest efficiency of a transmission line are used. Power losses by wire corona transmission losses are considered.